No ritmo do compasso, a melodia das filarmônicas em harmonia com o tempo: um estudo sobre a Lyra Ceciliana e a Minerva Cachoeirana (1960-1980) - Cazaes, Melira Elen Mascarenhas (2015)
The present work aims to analyze Cachoeira Town’s Lyra Ceciliana and Minerva Cachoeirana Philharmonics, respectively founded in 1870 and 1878. Such a work shows a study concerning the above-mentioned Institutions covering the period from 1960 to 1980, in order to identify the Philharmonics members’ profiles, their partners and leading groups; events in which both Institutions used to participate, the type of audience that accompanied them and the relationships between the Philharmonics and that time municipal government. The work also exhibits the tours of various locations accomplished by the above-mentioned Philharmonics, as well as the conflicts between them upon showing off in the garden bandstands concerts. We have chosen the time frame among the years 1960 to 1980, seeking to identify the cultural, social and technological transformations in Brazil and in Cachoeira Town during that period and the impacts the Military Dictatorship caused in Cachoeira’s Philharmonics. The issue that guided the research was based upon the following question: what survival strategy were developed by both Philharmonics to keep themselves alive and resistant to the pressures imposed by the diffusion of new technologies, new rhythms and sounds? In order to obtain answers to our questions we have used several sources, such as minutes of meetings, members’ book, the institution regulations, articles, photographs, newspapers and interviews with both Philharmonics musicians. This research accomplishment is justified considering it provides a thorough analysis about the above-metioned Philharmonics, also due to what they have promoted and are currently developing social and educational work of great relevance to not only the town but also other locations’ teenagers and young adults.